Plot Monitoring Survey - Ouerghemmi, Hassen; Frija, Aymen; Rekik, Mourad; Devkota Wasti, Mina Kumari (International Center for Agricultural Research in the Dry Areas, 2023)
The XLS form will be programmed in mobile data collection tool (ODK) in order to generate data on Experimental plots in the Tunisian Agroecological Living Landscape during the initiative implementation period.